Efficiency analysis with non parametric method: illustration of the Tunisian ports - Hlali, Arbia (Logistics and sustainable transport, 2018)
This paper applies a non-parametric method to provide level technical efficiency for 7 Tunisian ports during 18 years (1998-2015). These ports represent different data set. The use of the model of variable returns to scale (VRS) has led to interesting results. The results show that the most ports are characterized by low levels of technical efficiency, with the exception port of Rades. In addition, the result shows the variation of variable returns to scale and constant returns to scale of technical port’s efficiency. Furthermore, we concluded that the panel data improves the efficiency estimates.
Keywords: neparametrična analiza; non parametric analysis; technical efficienct; tehnična učinkovitost; Tunisian ports; tunizijska pristanišča